CRISPR-Cas Systems in Helicobacter pylori: A Genomic Insight into Antibiotic Resistance Mechanism: Sistem CRISPR-Cas pada Helicobacter pylori: Wawasan Genomik tentang Mekanisme Resistensi Antibiotik - Al-Haidary, Muhammad Abdul-Razzaq Ali; J, Abed Abbas; MH, Al-Bayati (Universitas Muhammadiyah Sidoarjo, 2025)
Helicobacter pylori, a Gram-negative bacterium infecting half of the world's population, presents increasing challenges as antibiotic resistance continues to grow. This research explores the lesser-studied function of CRISPR-Cas systems in influencing H. pylori's resistance to primary antibiotics (clarithromycin, metronidazole, levofloxacin). By utilizing whole-genome sequencing and phenotypic assessment of 350 clinical isolates, we show that CRISPR-positive strains (45.7%) have notably lower resistance rates compared to CRISPR-negative strains (clarithromycin: 62.5% vs 84.2%, *p*=0.001; metronidazole: 56.3% vs 73.7%, *p*=0.003). Type I CRISPR systems displayed the most significant negative correlation with resistance (*r*=-0.63), which is linked to their targeting of resistance plasmids (20% spacer matches) and the repression of mobile genetic elements (IS605 prevalence: 22% compared to 68% in CRISPR-negative strains, *p*<0.001). Phylogenetic analysis showed that CRISPR(+) strains create unique clades with lower genomic diversity, indicating CRISPR's role in stabilizing against horizontal gene transfer. Statistical modeling validated CRISPR as a standalone predictor of clarithromycin susceptibility (OR=0.42, 95% CI:0.24–0.71). These results highlight CRISPR-Cas as a natural obstacle to the evolution of resistance in H. pylori, with possible applications for CRISPR-driven diagnostics and strategies for reversing resistance. The research tackles important knowledge deficiencies in prokaryotic defense systems and suggests innovative strategies to fight antimicrobial resistance in this crucial pathogen. Highlights: CRISPR (+) H. pylori strains show significantly lower resistance to clarithromycin, metronidazole, and levofloxacin compared to CRISPR (−) strains. Type I CRISPR systems offer the strongest resistance protection, with a notable negative correlation to resistance gene acquisition (r = -0.63). CRISPR spacers target resistance-related plasmids, suggesting a natural mechanism to block horizontal gene transfer of antibiotic resistance traits Keywords: CRISPR-Cas, H. pylori, Antibiotic Resistance, Genomics, Plasmid Transfer